Relational Database Robustness, Performance and Security - Kiukas, Jonne (My University, 2024)
This thesis examines relational databases, which are foundational to modern information systems due to their structured design and ability to store, retrieve, and manage data. The thesis focuses on three important aspects of relational databases, robustness, performance, and security. The goal is to identify the key characteristics that define a robust database, analyze factors affecting performance, and explore potential security threats and prevention measures. To assess robustness, the thesis identifies transaction management, data availability, ACID properties, concurrency control, deadlock prevention, and other characteristics as crucial factors. Performance is evaluated by analyzing hardware resources, network efficiency, use of indexes, and query optimization techniques. For security, the study highlights common threats such as SQL injection, unauthorized access, and employee misuse, alongside preventive measures like prepared statements, access control, encryption, auditing and penetration testing. The thesis involves tables that summarize findings and provides answers to the research questions. The findings presented in this thesis are designed to serve as a guide for decision-makers in evaluating and selecting the appropriate database for their organization. With the help of this thesis the company can make the right adjustments that increase the customer and user satisfaction.
Keywords: relational database, database management system, robustness, performance, security